PEMBERDAYAAN KOMUNITAS PESISIR HUANGOBOTU: PELATIHAN DAN PENDAMPINGAN PRODUKSI PUPUK KERING LIMBAH IKAN TPI INENGO BERBASIS AKTIVATOR MIKROBA - Wila Rumina Nento; Shindy Hamidah Manteu; I Made Sudiarta (Universitas Mataram, 2026)
This community service program aims to empower the coastal community of Huangobotu Village through an innovative approach to utilizing organic waste from the Inengo Fish Auction House (TPI) by converting it into nutrient-rich dry fertilizer. Organic waste generated from auction activities—such as fish residues, entrails, bones, skin, and scales—has not been optimally utilized. This condition has led to various environmental problems, including unpleasant odors, water pollution, and declining sanitation around the TPI area. Limited knowledge and inadequate waste-processing technology have further exacerbated the situation. Therefore, community empowerment initiatives are needed to transform this waste into more valuable products. Through a participatory approach, the implementing team engaged coastal residents, particularly youth groups (karang taruna), in technical training and mentoring for the production of dry fertilizer. The activities included raising awareness of proper waste management, demonstrating processing techniques, and applying simple methods using microbial activators. The results showed an increase in participants’ knowledge and skills in converting organic waste into useful, marketable fertilizer. Participants were able to independently apply basic processing techniques using microbial activators. Management and production levels improved by 70% and 75%, respectively, indicating the program’s effectiveness in enhancing awareness of proper waste handling. Beyond addressing environmental issues, the program also fostered greater understanding of circular economy practices within the community. Furthermore, the dry fertilizer innovation has encouraged the emergence of local business opportunities based on fishery waste. This waste-management model is expected to contribute to reducing coastal pollution and supporting environmentally friendly agricultural development in Gorontalo. The program effectively strengthened the community’s capacity in processing organic waste, and the dry fertilizer innovation has strong potential as a sustainable waste-management solution.